2011
DOI: 10.1021/la204299h
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Resistant Ultraflat Gold Using Liquid Glass

Abstract: Templating against atomically flat materials allows creation of smooth metallic surfaces. The process of adding the backing (superstrate) to the deposited metals has proven to be the most difficult part in producing reliable, large-area, solvent-resistant substrates and has been the subject of recent research. In this paper we describe a simple and inexpensive liquid glass template-stripping (lgTS) method for the fabrication of large area ultraflat gold surfaces. Using our lgTS method, ultraflat gold surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…To rule out the possibility that roughness might play a role in the enhancement, Au surfaces with a very high degree of flatness were prepared by a templatestripping method against mica. 25 These Au surfaces, with a root-mean-square (rms) roughness of 0.3 nm, showed similar levels of enhancement to the normal flat Au surfaces fabricated by thermal evaporation (Supporting Information Figure S1). Neither type of Au substrate showed any molecular signal in the absence of MONPs, confirming that Raman enhancements indeed only arise from the interaction between the MONPs and Au surfaces.…”
mentioning
confidence: 73%
“…To rule out the possibility that roughness might play a role in the enhancement, Au surfaces with a very high degree of flatness were prepared by a templatestripping method against mica. 25 These Au surfaces, with a root-mean-square (rms) roughness of 0.3 nm, showed similar levels of enhancement to the normal flat Au surfaces fabricated by thermal evaporation (Supporting Information Figure S1). Neither type of Au substrate showed any molecular signal in the absence of MONPs, confirming that Raman enhancements indeed only arise from the interaction between the MONPs and Au surfaces.…”
mentioning
confidence: 73%
“…[13] Later, Hatton et al [14] reported optical transmission measurements on ultra-thin gold films deposited on silanized glass, but did not compare the results to a detailed structural analysis or theoretically expected transmission spectra. The method of surface activation with mercapto-silane is easier and less costly than some other fabrication procedures reported recently [15,16] and does not compromise the optical quality of ultra-thin films, as is the case when metallic adhesion/seeding layers (typically Ti, Cr, Ge or Ni) are used. [17] It should be noted that a substantial amount of research has also been devoted to ultra-thin silver films and their optical properties, where many of the same problems and applications are encountered.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach involves evaporating Au on a mica substrate and then peeling it off from the initial substrate and attaching to a silica one [55,56]. This approach allows for extremely flat layers (RMS = 0.275 nm [55]) to be created (Figure 3), but it does not preclude the use of Reproduced with permission from [55].…”
Section: Gold Thin Filmsmentioning
confidence: 99%
“…This approach allows for extremely flat layers (RMS = 0.275 nm [55]) to be created (Figure 3), but it does not preclude the use of Reproduced with permission from [55]. metallic adhesion layers in order to insure good adhesion between the silica superstrate and the gold.…”
Section: Gold Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation